Rare earth concentration dependence on the glass optical properties in the system CaOGeO2Li2OB2O3 (RE = Dy3+). (2022) - Koseva, I.; Nikolov, V.; Gancheva, M.; Aleksandrov, L.; Ivanov, P.; Petrova, P.; Iordanova, R.; Tomova, R.
Abstract: Dy 3+ doped glasses from the oxide system CaOGeO2 Li2 OB2 O3 with different compositions were prepared by melt quenching technique. The obtained glass samples were characterized by X-ray diffraction (XRD), Differential thermal analyses (DTA), Infrared spectroscopy (IR) and Photoluminescence (PL) measurements. The X-ray analysis reveals amorphous nature of the samples. Thermal stability of the doped glasses depends more on the glass composition than the dopant concentration. IR analyses confirm some changes in the local structures of the glasses after doping. The excitation and emission spectra show typical for Dy 3+ ions lines with domination of yellow emission peak. CIE coordinates and yellow-to-blue ratio of the obtained glasses is with almost the same values, therefore almost the same emitted color is expected.